Structure-activity relationship study of mesyl and busyl phosphoramidate antisense oligonucleotides for unaided and PSMA-mediated uptake into prostate cancer cells - Sergeeva, O.; Akhmetova, E.; Dukova, S.; Beloglazkina, E.; Uspenskaya, A.; Machulkin, A.; Stetsenko, D.; Zatsepin, T. (Frontiers in Chemistry, 2024)
Phosphorothioate (PS) group is a key component of a majority of FDA approved oligonucleotide drugs that increase stability to nucleases whilst maintaining interactions with many proteins, including RNase H in the case of antisense oligonucleotides (ASOs). At the same time, uniform PS modification increases nonspecific protein binding that can trigger toxicity and pro-inflammatory effects, so discovery and characterization of alternative phosphate mimics for RNA therapeutics is an actual task. Here we evaluated the effects of the introduction of several N-alkane sulfonyl phosphoramidate groups such as mesyl (methanesulfonyl) or busyl (1-butanesulfonyl) phosphoramidates into gapmer ASOs on the efficiency and pattern of RNase H cleavage, cellular uptake in vitro, and intracellular localization. Using Malat1 lncRNA as a target, we have identified patterns of mesyl or busyl modifications in the ASOs for optimal knockdown in vitro. Combination of the PSMA ligand-mediated delivery with optimized mesyl and busyl ASOs resulted in the efficient target depletion in the prostate cancer cells. Our study demonstrated that other N-alkanesulfonyl phosphoramidate groups apart from a known mesyl phosphoramidate can serve as an essential component of mixed backbone gapmer ASOs to reduce drawbacks of uniformly PS-modified gapmers, and deserve further investigation in RNA therapeutics.